The Westing game - Raskin, Ellen (New York Dutton, 1978)
The mysterious death of an eccentric millionaire brings together an unlikely assortment of heirs who must uncover the circumstances of his death before they can claim their inheritance.
Newbery Medal, 1979
Keywords: Inheritance and succession -- Fiction; Apartment houses -- Fiction; Mystery and detective stories; Humorous stories; Chicago (Ill.) -- Fiction